Magnetophoretic separation in microfluidic system. (2021) - Dagher, Sawsan; Hilal-Alnaqbi, Ali; Khashan, Saud; Alazzam, Anas
Abstract: It is still a challenge to develop a high-performance microdevice with high capture efficiency that can be used to separate magnetic microparticles from mixtures and release a target biomaterial on demand. A high aspect ratio continuous flow microdevice is developed that exploits magnetic manipulation for integrated capture and isolation of microparticles in a continuous flow. The main objective of this work is the utilization of a soft-magnetic wire (i.e. high magnetic gradient concentrator) in a way that the separation efficiency can be simply scaled up by increasing the length of the wire (i.e. traversing the flow direction). The results demonstrated that when the magnetic field is applied the wire becomes magnetized and produces a local magnetic force that separates the magnetic particles from the flow. The separation of magnetic particles in free flow strongly depends on the flow rate, since the separation efficiency is decreased as the flow rate increased, and showed perfect capture efficiency with the optimized flow rates. The magnetic particles separation is studied for two cases; the wire is invasive and non– invasive through the fluid flow. Overall, the results verified the capability of the device to separate magnetic microparticles from a suspension with high sensitivity, specificity, reproducibility and at throughputs scalable with the depth of the microchannel. That will satisfy the requirements to bring cell separation into clinical utility.